Diatom responses to late-glacial and early-Holocene environmental changes at Krakenes, western Norway - Bradshaw, EG; Jones, VJ; Birks, HJB; Birks, HH (KLUWER ACADEMIC PUBL, 2000)
A stratigraphic diatom sequence is presented for the period from 13,870-9,170 cal BP from Krakenes Lake, western Norway. Changes in species assemblages are discussed with reference to the changing environmental conditions in the Allerod, Younger Dryas, and the early Holocene and to the development of the aquatic ecosystem. The site is sensitive to acidification, and diatom-based transfer functions are applied to estimate the past pH status. The combination of rapid sediment accumulation together with an excellent calibrated radiocarbon chronology means that the rate of inferred pH change and associated increase in [H+] can be assessed and compared with recent, anthropogenically acidified situations.The Allerod diatom assemblages are dominated by benthic taxa particularly Fragilaria species, indicating an unproductive, alkaline, turbid, and immature system. Diatoms are absent in the early part of the Younger Dryas, but subsequently a sparse planktonic flora develops reflecting decreased turbidity and/or increased nutrient supply. A clear sequence of diatom assemblages is seen in the early Holocene. A short-lived peak of Stephanodiscus species indicating a period of increased nutrient availability occurred at ca. 11,500 cal BP. Throughout the early Holocene, acid-tolerant species increasingly replaced less acidophilous, circumneutral taxa.The lake became slightly more acid during the Allerod, but this was statistically insignificant in a trend test involving regression of pH or [H+] in relation to age. Diatom-inferred pH declined rapidly during the early Holocene period investigated (9,175-11,525 cal BP) with a statistically significant overall rate of 0.024 pH units per 100 yrs. This consisted of an older (ca. 11,525-10,255 cal BP) phase, where pH fell more rapidly at up to 0.095 pH units per 100 yrs; and a younger phase after ca. 10,500 cal BP where the pH fall was extremely slow (0.008 pH units per 100 yrs) and was not statistically significant.In the Allerod a combination of low catchment productivity together with disturbance, weathering, and minerogenic inwash ensured that the base-cation status remained relatively high. In the Holocene the catchment soils stabilised and base cations were sequestered by terrestrial vegetation and soil. This resulted in reduced base-cation leaching and this, together with the production of organic acids caused the lake to acidify, reaching an equilibrium by ca. 10,000 cal BP.